The effect of clay in the formulation of non-traditional completion fluid for underbalance perforation - Khalil, M.; Mohamed Jan, B.; Abdul Raman, Abdul Aziz (2009)
In the last decade, majority of works in the upstream oil and gas industry relate to the use of clay are always associated with drilling fluid. Clay is added in drilling fluids for viscosity control to aid the transfer of cuttings from the bottom of the well to the surface, and for filtration control to prevent filtration of drilling fluids into the pores of productive formations. This paper presents the use of clay in formulating non-traditional completion fluid to ensure the successful of perforation job and lead to the increment of production rate. Clay is used as homogenizing agent to create a stable and non-damaging low-density completion fluid. In this work a series of investigation i.e., FTIR, SEM, and particle size analysis were conducted to determine the effect of clay in formulating low density completion fluids. Results indicate that the addition of natural clay dramatically increase the stability of the final fluids. However, reducing the particle size and acid-activation of the clay does not positively affect the fluid stability.